Slang Words Analysis in The Movie Ralph Breaks The Internet - Prabu Sulaiman Syahputra; Dewi Syafitri (EDULIA: English Education, Linguistic and Art Journal, 2022)
This research aimed to analyzing the types of slang word that found in Ralph Breaks the Internet (2018) movie. The research method is qualitative approach, which is the researcher analyze the movie based on the theory by Allan and Burridge (2006) about the slang words that used as references. Technique of analyze the data is by watching the movie and transcribe the dialogue from movie. The results of the research showing there are four types of slang word that found in the Ralph Breaks the Internet movie. Moreover, there are 50 slang words types that the researcher found based on the Allan and Burridge theory included fresh and creative (24), immitative (17), flippant (7) and clipping (2). The most dominant of slang word is fresh and creative, which means there is so many new vocabulary from old words used or actually a brand new word that spoken by its character. The meaning of slang words that found in the movie is various, but those slang words are mostly used in informal situations. In conclusion, hopefully this research can be the one of the references for the other researchers. Keywords: Language, Linguistic, Movie, Slang